Information and Communication Technology (ICT) in Nigerian Educational System - Agbetuyi, P. A.; Oluwatayo, J. A. (Mediterranean Journal of Social Sciences, 2012)
In this present age of globalization, information and communication technology has transformed the Nigerian Educationalsystem positively. This paper therefore discusses the correlate existing between information and communication technology andeducation and the extent to which it has affected the Nigerian system of education. The setback and obstacles to its full actualization isalso examined.